Can the limited marsupium space be a limiting factor for Syngnathus abaster with size-assortative mating - Silva, K. (2008)
1. Some syngnathid species show varying degrees of sex role reversal aside from male pregnancy, with females competing for access to mates and sometimes presenting conspicuous secondary sexual characters. Among other variables, brooding space constraints are usually considered a key element in female reproductive success, contributing strongly to the observed morphological and behavioural sexual differences. Nevertheless, a close relationship between sex role reversal and male brooding space limitation has not yet been accurately demonstrated in field studies. 2. The present work, conducted over two consecutive breeding seasons in a wild population of the sex role-reversed pipefish Syngnathus abaster , simultaneously analysed egg number and occupied space, as well as the free area in the male’s marsupium. The number of eggs that would fit in the observed unoccupied space was estimated. 3. Contrary to what would be expected, given the marked sexual dimorphism observed in the population studied, where females were larger and more colourful, male brooding space did not appear to limit female reproduction as neither large nor small individuals presented a fully occupied pouch. Interestingly, the largest unoccupied areas of marsupium were found in the larger individuals, although they received more and larger eggs. Laboratory data also showed that larger females lay larger eggs. 4. Together, these results suggest the existence of assortative mating, which may result from: (i) the reluctance of larger males (which tend not to receive small eggs usually laid by small females) to mate with lower quality females, even at the expense of a smaller number of offspring; or (ii) female– female competition, which might strongly reduce the hypothesis of a small female mating with a large male. The potential impact of temperature on reproduction and population dynamics is also discussed in the light of ongoing climatic changes.